The Effect of Using Strip Story Media to Improve Writing Skills in Learn Arabic among Students at State Junior High School 1 Hiliran Gumanti, West Sumatra - Ummah, Khuntum Khaira; Amrullah, Abdul Malik Karim; Kholil, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Learning media is one of the important elements in the success of the learning process, especially Arabic language learning. Appropriate learning media helps students understand the learning materials delivered by the teacher. Strip story media is a very effective learning media in learning Arabic writing skills. This study aims to analyze the effect of strip story media on improving students' writing skills. The research approach used is Quantitative Research. This type of research is a quasi-experimental design with a pretest-posttest control group design. The subjects of this study were students of class VIII 1 as the control class and class VIII 3 as the experimental class in a junior high school. The research instruments included pre-test and post-test questions to measure the level of students' writing skills. The data obtained were analyzed using statistical tests to determine the differences in learning outcomes between the control class and the experimental class. The results showed that there were significant differences between the two classes. With the comparative value of the mean results at the time of the pretest and posttest, namely the pretest in the experimental class 57.1 with the Dhaif criteria and the posttest 72.1 with the Maqbul criteria, while the pretest in the control class 56.8 with the Dhaif criteria and the posttest 61.8 with the Dhaif criteria too. Students who learn with strip story media experience a greater increase in writing skills compared to students in the control class. Thus, strip story media can be used as an effective alternative in Arabic language learning to improve students' writing skills.